Histories of prostitution in Central, East Central and South Eastern Europe - Dolinsek, Sonja; Saryusz-Wolska, Magdalena 1980-; Verlag Ferdinand Schöningh (Fokus, 2023)
This edited collection comprises twelve original research papers scrutinizing the historical dimensions of prostitution across 19th and 20th century Central, South, and East-Central Europe. Each contribution employs distinct methodological perspectives and diverse sources. Notably, this volume includes pioneering articles delineating nearly uncharted terrains in the history of prostitution in Europe, especially socialist Eastern European countries. The volume is intended primarily for scholars and students specializing in women's history, gender studies, and sexualities, as well as histories of crime and policing with a focus on European or Global History